Kidney transplant in Uruguay - Balboa, Oscar (Cirugía del Uruguay, 2002)
Results of 546 Transplants are presented Renal (TR) performed by a multidisciplinary team, in a period of twenty years. Survival would act! ten years from patients is 80% and kidneys 45%. In an analysis multivariate is verified in the last five years a significant difference in the survival of the kidney if there was no initial renal failure, interpreting the latter, as a consequence of a greater experience of the group, a good percentage of cadaveric donors, 81%, with a good number of donors per million inhabitants when compared to Latin America, but what does not stand up to comparison with the possible percentages, both in Uruguay and in other countries. Finally, the need to improve is emphasized organ procurement.